DEVELOPMENT OF A BROMOPYROGALLOL RED-IMMOBILIZED SORBENT FOR THE SORPTION-SPECTROPHOTOMETRIC DETERMINATION OF Pb(II) IONS - Abdunabiyeva Mashkhura Mashrab kizi, Abdumurodova Nozima Akmal kizi,Kosimova Khurshida Rajabboyovna (International Journal of Literature and Language Studies, 2026)
The determination of Pb(II) ions at trace levels is essential for environmental monitoring and public health protection because of the high toxicity, persistence, and bioaccumulative nature of lead. In this study, a Bromopyrogallol Red (BPR)-immobilized sorbent was developed for the sorption-spectrophotometric determination of Pb(II) ions in aqueous media. The sorbent was prepared by immobilizing Bromopyrogallol Red onto a silica gel matrix, providing a stable and highly active surface for the selective adsorption of Pb(II) ions. The effects of solution pH, contact time, sorbent dosage, and initial Pb(II) concentration were systematically optimized to establish the optimum analytical conditions. Under the optimized conditions, the developed sorbent exhibited excellent adsorption efficiency, high sensitivity, and good selectivity toward Pb(II) ions. The proposed method demonstrated satisfactory linearity, precision, accuracy, and reproducibility, confirming its suitability for trace lead determination. Furthermore, the method was successfully applied to environmental water samples with satisfactory recovery values. The developed sorption-spectrophotometric procedure offers a simple, rapid, cost-effective, and environmentally friendly alternative for the routine determination of Pb(II) ions.